Biomechanical characteristics of hammer throwing technique - Song Haiming (Theory and Practice of Physical Culture, 2025)
Objective of the study. To study the biomechanical characteristics of hammer throwing technique. Methods and structure of the study. To determine the biomechanical characteristics of the hammer throwing technique, 3 attempts were made by all participants of the experiment with mandatory shooting by high-speed video cameras KASIO with a frequency of 120 frames per minute. The sample size of athletes of CG and EG was 10 observations for each investigated kinematic parameter. A total of 75 hammer throw attempts were recorded and 675 kinematic parameters were processed. We used APAS (Ariel Performance Analysis System) 3D video motion analysis system for video analysis and processing. Results and conclusions.. Comparing the relevant technical parameters with outstanding athletes in the world, it can be seen that the acceleration rhythm of Chinese hammer throwers in each lap fluctuates greatly during the rotation process, the center of gravity moves slowly and the acceleration time is especially inaccurate. At the same time, this is due to factors such as insufficient forward body inclination, right leg extension, little movement of the right foot on the ground, and slow landing speed. The rhythm of body rotation and the rhythm of hammertoe rotation were clearly raised, and it was pointed out that during single-supported rotation, the athlete increased the speed of the hammertoe end by increasing the angular velocity, while during the double-supported period, the speed of the hammertoe end was maintained by increasing the radius, thus achieving control of the equipment.